Unmasking Reflexivity in HR Managers During the COVID-19 Lockdown in Italy - Ripamonti, Silvio Carlo; Galuppo, Laura; Provasoli, Giulia; Benozzo, Angelo (Frontiers in Psychology, 2020)
In this paper we explore how some Italian HR managers narrate the changes imposed by the COVID-19 threat in the workplace. What has happened in the world since December 2019 has been an exceptional event to which HR managers have reacted in very different ways, and we were interested in understanding how HR managers came to introduce the organizational changes aimed at coping with the emergency, as well as how employees were involved in those organizational changes. The article is based on a thematic analysis of some interviews with Italian HR managers whose companies decided to resort to working from home on a massive scale. We wanted to offer some reflections on the actions taken by a few HR managers and Italian companies to keep working at a time when most of the workers were forced to respect the lockdown.